Linear Mitochondrial Genome in Anthozoa (Cnidaria): A Case Study in Ceriantharia - Stampar, Sérgio N. [UNESP]; Broe, Michael B.; Macrander, Jason; Reitzel, Adam M.; Brugler, Mercer R.; Daly, Marymegan (Springer Nature, 2019)
Sequences and structural attributes of mitochondrial genomes have played a critical role in the clarification of relationships among Cnidaria, a key phylum of early-diverging animals. Among the major lineages of Cnidaria, Ceriantharia (“tube anemones”) remains one of the most enigmatic in terms of its phylogenetic position. We sequenced the mitochondrial genomes of two ceriantharians to see whether the complete organellar genome would provide more support for the phylogenetic placement of Ceriantharia. For both Isarachnanthus nocturnus and Pachycerianthus magnus, the mitochondrial gene sequences could not be assembled into a single circular genome. Instead, our analyses suggest that both species have mitochondrial genomes consisting of multiple linear fragments. Linear mitogenomes are characteristic of members of Medusozoa, one of the major lineages of Cnidaria, but are unreported for Anthozoa, which includes the Ceriantharia. The inferred number of fragments and variation in gene order between species is much greater within Ceriantharia than among the lineages of Medusozoa. We identify origins of replication for each of the five putative chromosomes of the Isarachnanthus nocturnus mitogenome and for each of the eight putative chromosomes of the Pachycerianthus magnus mitogenome. At 80,923 bp, I. nocturnus now holds the record for the largest animal mitochondrial genome reported to date. The novelty of the mitogenomic structure in Ceriantharia highlights the distinctiveness of this lineage but, because it appears to be both unique to and diverse within Ceriantharia, it is uninformative about the phylogenetic position of Ceriantharia relative to other Anthozoa. The presence of tRNA Met and tRNA Trp in both ceriantharian mitogenomes supports a closer relationship between Ceriantharia and Hexacorallia than between Ceriantharia and any other cnidarian lineage, but phylogenetic analysis of the genes contained in the mitogenomes suggests that Ceriantharia is sister to a clade containing Octocorallia + Hexacorallia indicating a possible suppression of tRNA Trp in Octocorallia.